2019
DOI: 10.1167/tvst.8.6.3
|View full text |Cite
|
Sign up to set email alerts
|

Presymptomatic Retinal Sensitivity Changes in Intermediate Age-Related Macular Degeneration Associated With New Retinal Fluid

Abstract: PurposeTo determine whether change in retinal sensitivity in areas with subretinal or intraretinal fluid secondary to age-related macular degeneration (AMD) precedes visual symptoms. If confirmed, retinal sensitivity testing could be used for home monitoring in AMD.MethodsIndividuals with intermediate AMD enrolled in a longitudinal study were seen every 6 months and underwent best-corrected visual acuity testing (BCVA), spectral domain–optical coherence tomography (SD-OCT), and microperimetry. Asymptomatic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Instead, improved methods of risk stratification to identify individuals at a high risk of developing nAMD that require more frequent monitoring using OCT imaging may be a more effective approach, given the effectiveness of this imaging modality for the early detection of nAMD. 10 In particular, the introduction of OCT angiography into most commercial OCT systems may enable the identification of those with subclinical, nonexudative neovascularization that confer a high risk of developing exudation that warrant such increased monitoring frequency. 31 Technological advances leading to the development of low-cost OCT imaging systems could also enable self-monitoring in high-risk individuals as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, improved methods of risk stratification to identify individuals at a high risk of developing nAMD that require more frequent monitoring using OCT imaging may be a more effective approach, given the effectiveness of this imaging modality for the early detection of nAMD. 10 In particular, the introduction of OCT angiography into most commercial OCT systems may enable the identification of those with subclinical, nonexudative neovascularization that confer a high risk of developing exudation that warrant such increased monitoring frequency. 31 Technological advances leading to the development of low-cost OCT imaging systems could also enable self-monitoring in high-risk individuals as well.…”
Section: Discussionmentioning
confidence: 99%
“…Although microperimetric sensitivity is reduced over regions with the earliest signs of late AMD (including nAMD 9,10 and atrophic AMD 12 ), such reductions may also occur in regions affected by intermediate AMD lesions, such as large retinal pigment epithelium elevation, 8,22,23 marked ellipsoid zone disruptions, 8,23 or numerous hyperreflective foci on OCT imaging. 24 Along with the known test-retest variability of microperimetry testing, 19 detecting the earliest onset of late AMD is expected to be challenging and was reflected in the poor performance of microperimetry in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, SRF might be interpreted more as a biomarker of efficient disease management preventing IRF and bleeding, and less as a by itself protective factor. On the contrary, the sole appreciation of visual acuity might represent an only partial view on visual function; several studies have recently shown that sub-retinal fluid significantly reduces retinal sensitivity, which might impair visual performance especially under low-luminance 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…36 Given that the retinal sensitivity may be a useful parameter for assessing the functional status of the retina in AMD, 37 1 might predict that MP may be able to detect decreased retinal sensitivity in areas that would develop subretinal fluid and/or intraretinal fluid, and subsequent visual acuity reductions. Wightman et al 38 reported that MP could detect localized loss of retinal sensitivities in regions with fluid without any apparent change in the best-corrected visual acuity (BCVA) or the Amsler grid findings. This would then highlight the possibility of MP in detecting these early subtle functional alterations before the development of the exudations (Fig.…”
Section: Neovascular Amdmentioning
confidence: 99%